2009
DOI: 10.1159/000199465
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive-Protein Levels Associated with Infection Predict Short- and Long-Term Outcome after Supratentorial Intracerebral Hemorrhage

Abstract: Background: The aim of the current study was to assess the occurrence of infection and its impact on the short- and long-term outcome of patients with supratentorial intracerebral hemorrhage (ICH). Methods: 247 patients suffering from supratentorial ICH were extracted from our local stroke database. Complete data sets including long-term functional outcome measured by the modified Rankin Scale (mRS), and baseline computed tomography data could be obtained in 113. The charts of these patients were screened for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…CRP level in patients suffering supratentorial intracerebral hemorrhage with infection during their hospital stay is an independent predictor of poor stroke outcome. 21 In the present study we found that both the serum CRP level and hematoma volume were predictors of short-term mortality after sICH. The serum ROOH level was found to correlate with mortality, but it did not appear to be a predictor of early lethal outcome.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…CRP level in patients suffering supratentorial intracerebral hemorrhage with infection during their hospital stay is an independent predictor of poor stroke outcome. 21 In the present study we found that both the serum CRP level and hematoma volume were predictors of short-term mortality after sICH. The serum ROOH level was found to correlate with mortality, but it did not appear to be a predictor of early lethal outcome.…”
Section: Discussionsupporting
confidence: 52%
“…The disability status assessed by the Mathew Scale was 46 (32-60) points. The NIHSS neurological deficit 1 week after stroke onset was 19 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) points. Twenty-eight per cent of the patients died during the first week, and 76% of the survivors had a poor outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results, patients were classified into 4 groups as described previously. 20 The first group included patients with pneumonia; diagnosis was based on clinical criteria including fever, purulent sputum, or respiratory deterioration and positive chest radiographs in combination with laboratory findings of leukocytosis and CRP Ͼ50 mg/L. 21,22 The second group comprised patients with urinary tract infections diagnosed based on elevated leukocyte count and positive nitrite in the urine screening in combination with leukocytosis and CRP Ͼ50 mg/L.…”
Section: Assessment Of Infectionmentioning
confidence: 99%
“…An increased incidence of hemorrhagic stroke has also been noted following upper respiratory infection due to the increased likelihood of formation and rupture of cerebral aneurisms, leading to SAH (Kunze et al, 2000 ). Furthermore, in a study examining incidence of infection in ICH patients, those that had infection had significantly larger hemorrhages, poorer National Institutes of Health Stroke Scale scores, raised levels of CRP and were more likely to experience intraventricular hemorrhage extension (Diedler et al, 2009 ). A causal relationship between stroke and infection is supported by overlap of pathways that are common to both, including inflammation and thrombosis.…”
Section: Pre-existing Systemic Inflammation and Stroke Incidencementioning
confidence: 99%